A Comparison of the Effectiveness of Written Instructions and Multimedia Tutorials for Call of Duty: Modern Warfare 2 - Klugh, Josh (Missouri Southern State University (Joplin, Mo.), 2011)
Abstract: Examines the differences between multimedia tutorials and written instructions while comparing their effectiveness in teaching a specific task. A comparison of the performance of two test groups (one group using written instructions and one using a multimedia tutorial) on the difficulty-recommendation level of Modern Warfare 2 (MW2).--p. 2.; 28 pages : PDF file ; cm.